Bleeding risk by intensity of anticoagulation in critically ill patients with COVID‐19: A retrospective cohort study. (7th May 2021) - Halaby, Rim; Cuker, Adam; Yui, Jennifer; Matthews, Andrew; Ishaaya, Ella; Traxler, Elizabeth; Domenico, Christopher; Cooper, Tara; Tierney, Ann; Niami, Pardis; van der Rijst, Nathalie; Adusumalli, Srinath; et al.
Abstract: Background: Studies report hypercoagulability in coronavirus disease 2019 (COVID‐19), leading many institutions to escalate anticoagulation intensity for thrombosis prophylaxis. Objective: To determine the bleeding risk with various intensities of anticoagulation in critically ill patients with COVID‐19 compared with other respiratory viral illnesses (ORVI). Patients/Methods: This retrospective cohort study compared the incidence of major bleeding in patients admitted to an intensive care unit (ICU) within a single health system with COVID‐19 versus ORVI. In the COVID‐19 cohort, we assessed the effect of anticoagulation intensity received on ICU admission on bleeding risk. We performed a secondary analysis with anticoagulation intensity as a time‐varying covariate to reflect dose changes after ICU admission. Results: Four hundred and forty‐three and 387 patients were included in the COVID‐19 and ORVI cohorts, respectively. The hazard ratio of major bleeding for the COVID‐19 cohort relative to the ORVI cohort was 1.26 (95% confidence interval [CI]: 0.86–1.86). In COVID‐19 patients, an inverse‐probability treatment weighted model found therapeutic‐intensity anticoagulation on ICU admission had an adjusted hazard ratio of bleeding of 1.55 (95% CI: 0.88–2.73) compared with standard prophylactic‐intensity anticoagulation. However, when anticoagulation was assessed as a time‐varying covariate and adjusted for other risk factors for bleeding, the adjusted hazard ratio for bleeding on therapeutic‐intensity anticoagulation compared with standard thromboprophylaxis was 2.59 (95% CI: 1.20–5.57). Conclusions: Critically ill patients with COVID‐19 had a similar bleeding risk as ORVI patients. When accounting for changes in anticoagulation that occurred in COVID‐19 patients, therapeutic‐intensity anticoagulation was associated with a greater risk of major bleeding compared with standard thromboprophylaxis.